Electron radiotherapy (IOERT) for applications outside of the breast: Dosimetry and influence of tissue inhomogeneities. (January 2020) - Avanzo, Michele; Dassie, Andrea; Chandra Acharya, Prabhu; Chiovati, Paola; Pirrone, Giovanni; Avigo, Cinzia; Barresi, Loredana; Dang Quoc, Soai; Fiagbedzi, Emmanuel; Navarria, Federico; Palazzari, Elisa; Bertola, Giulio; et al.
Highlights: In-phantom commissioning of the Mobetron was performed and externally validated. We measured dose enhancement factor of bone in IOERT up to 6% with energy 12 MeV and 3 cm applicator. In vivo dosimetry on 126 patients for treatments out of breast resulted in average +3.1% dose difference. Discrepancies of in vivo to prescribed doses may be also explained with presence of inhomogeneous tissues. Abstract: Purpose: The purpose of study is to investigate the dosimetry of electron intraoperative radiotherapy (IOERT) of the Intraop Mobetron 2000 mobile LINAC in treatments outside of the breast. After commissioning and external validation of dosimetry, we report in vivo results of measurements for treatments outside the breast in a large patient cohort, and investigate if the presence of inhomogeneities can affect in vivo measurements. Methods and materials: Applicator factors and profile curves were measured with a stereotactic diode. The applicators factors of the 6 cm flat and beveled applicators were also confirmed with radiochromic films, parallel-plate ion chamber and by an external audit performed with ThermoLuminescent Dosimeters (TLDs). The influence of bone on dose was investigated by using radiochromic films attached to an insert equivalent to cortical bone, immersed in the water phantom. In vivo dosimetry was performed on 126 patients treated with IOERT using metal oxide-silicon semiconductor field effect transistors (MOSFETs) placed on the tumor bed. Results: Relatively small differences were found among different detectors for measurements of applicator factors. In the external audit, the agreement with the TLD was mostly within ±0.2%. The largest increase of dose due to the presence of cortical bone insert was +6.0% with energy 12 MeV and 3 cm applicator. On average, in vivo dose was significantly (+3.1%) larger than prescribed dose. Conclusion: IOERT in applications outside the breast results in low discrepancies between in vivo and prescribed doses, which can be also explained with the presence of tissue inhomogeneity.